The Economic Losses of Surra Outbreak in Sumba Timur, Nusa Tenggara Timur-Indonesia - R. S. Dewi; R. Damajanti; A. H. Wardhana; S. Mulatsih; O. N. Poetri; W. Steeneveld; H. Hogeveen (Tropical Animal Science Journal, 2020)
Surra or trypanosomiasis outbreak occurred at Sumba Timur in 2010. Investigating the economic impact of an outbreak of Surra, especially in areas that were free of Surra before, has never been performed in Indonesia. The overall aims of this research are to analyze the economic impact of the Surra outbreak between 2010 and 2016 in Sumba Timur using a modified formula. Total economic losses were calculated by the sum of direct cost, indirect cost, and the other expenditure cost using primary and secondary data. Primary data were collected from interviews with 30 farmers, selected by multistage random sampling and from 2 livestock services officers. Secondary data were collected from The Livestock Services of Sumba Timur and The Diseases Investigation Center in Denpasar and The Local Quarantine Agency of Kupang. The result showed that the total economic loss caused by Surra was IDR (Indonesian Rupiah) 25.7 billion. The highest cost was indirect costs (46%), followed by the direct cost (37%) and control expenditure (17%). The highest proportion of the costs occurred in the years of 2011 and 2012, when the Surra outbreak started and when there was no control program in place. From the total of government expenditure related to the Surra outbreak, 64% of the total costs were part of the epidemic response program. The costs of prevention (maximal IDR 3.24 billion in 2013) were estimated to be lower than the costs of an outbreak (maximal IDR 5.04 billion in 2012). The high cost of outbreak was caused by the absence of a control program in place and the lack of knowledge of farmers about Surra diseases at the beginning of outbreak.